Phenethylammonium Iodide Passivation Layers for Flexible Planar Perovskite Solar Cells. Issue 11 (25th August 2022) - Lucarelli, Giulia; De Rossi, Francesca; Taheri, Babak; Brown, Thomas M.; Brunetti, Francesca
Abstract : Flexible perovskite solar cells (PSC) represent a viable technology for applications requiring high power‐to‐weight ratios, seamless integration onto a variety of shapes, and low embedded energy. Strategies to boost the performance of flexible PSC, which still lag behind their rigid counterparts, include passivation of the perovskite surface with ammonium salts. Herein, the optimization of low‐temperature solution‐processed phenethylammonium iodide (PEAI) layers to passivate triple‐cation perovskite films as an effective strategy for flexible planar PSCs is reported. The best PEAI‐passivated cell delivers a maximum power conversion efficiency of 15.2% in forward scan, which is 22% higher in relative terms compared with nonpassivated devices, due to a major improvement in both open‐circuit voltage and fill factor. Optoelectrical characterization highlights that PEAI films effectively reduce trap‐mediated charge recombination, without hindering charge transport across the perovskite/hole transport layer interface. Light‐soaking stability of nonencapsulated cells with PEAI layers is also greatly enhanced, retaining 80% of the initial power conversion efficiency for twice as long as the reference devices, therefore proving the potential of this material for the development of efficient and durable flexible PSCs. Abstract : Planar perovskite solar cells on flexible substrates show improved efficiency and stability thanks to the addition of low‐temperature solution‐processed phenethylammonium iodide (PEAI) passivation layers on top of the perovskite film. Several batches of flexible devices with different PEAI layer thicknesses are characterized in terms of performance, stability, and optoelectronic properties.